Corporate Investment and Asset Price Dynamics: Implications for the Cross‐section of Returns - CARLSON, MURRAY; FISHER, ADLAI; GIAMMARINO, RON (Journal of Finance, 2004)
ABSTRACT We show that corporate investment decisions can explain the conditional dynamics in expected asset returns. Our approach is similar in spirit to Berk, Green, and Naik (1999) , but we introduce to the investment problem operating leverage, reversible real options, fixed adjustment costs, and finite growth opportunities. Asset betas vary over time with historical investment decisions and the current product market demand. Book‐to‐market effects emerge and relate to operating leverage, while size captures the residual importance of growth options relative to assets in place. We estimate and test the model using simulation methods and reproduce portfolio excess returns comparable to the data.